Students' Perceptions of AI-Based Instruction in Academic Writing Course at an Indonesian Private University - Setiadi, Muhammad Astrianto; Basri, Muhammad; Sakkir, Geminastiti; Sardi, Ahmed; Rahman, Abd. (Universitas Negeri Makassar, 2025)
This study aims to find out how students perceive the integration of AI technology in learning academic writing. This qualitative case study examined the perceptions of 27 English students at Universitas Muhammadiyah Makassar regarding the use of AI tools in their academic writing development. Data were collected through semi-structured interviews, providing rich insights into students' attitudes, perceived benefits, and potential drawbacks of AI-driven instruction. The findings of this study show that there are two types of perceptions towards the application of AI in writing learning: Perceived usefulness and perceived ease of use. Perceived usefulness can be observed through several indicators, including improved academic writing quality, increased efficiency in writing activities, enhanced learning, better grades, and meeting writing requirements. Furthermore, perceived ease of use also has six indicators, namely ease of understanding, ease of use, clarity and understandability, flexibility and adaptability, minimal effort required, and user-friendliness.